Effect of Palmyrah (Borassus flabellifer L.) Fruit Pulp on Weight Gain of Mice - Ariyasena, Darshika D.; Jayasekara, Sharmini; Jansz, E.R.; Abeysekera, A.M. (My University, 2000)
Palmyrah (Borassusflabellifer L.) fruit pulp (PFP) contains a group of steroidal saponins called flabelliferins. One of these flabelliferins (a tetraglycoside) causes a bitter flavour in PFP, which detracts from the free use of PFP as a food. Techniques of debittering have been developed but these have suffered from the criticism that debittering could produce new saponins that may cause adverse nutritional effects. In this study, trials were conducted using outberd ICR mice. Experiments carried out with 6 weeks old (growing) mice with bitter PFP showed a statistically significant (p=(l.029) lowering of weight gain compared to the control feed (standard ratl mouse breeding feed) although food intake was nearly equal. Debittering of PFP with naringinase reversed the effect, in that there was no statistically significant difference between control and debittered PFP (p=O.88). Weight gain in the case of debittered PFP was higher than the bitter PFP (p=(l.()23). The study indicates that debittering does not produce adverse nutritional effects affecting weight gain but rather improves nutritional value of bitter PFP as judged by the weight gain. This may be due to. as revealed by a recent study. the bitter principle having an effect on active transport of nutrients.
Keywords: Palmyrah fruit pulp; Flabelliferins; ICR Mice